Aus erster Quelle. Beiträge zum 300-jährigen Jubiläum des Staatsarchivs der Freien und Hansestadt Hamburg - Frank, Joachim W.; Brakmann, Thomas; der Freien und Hansestadt Hamburg, Staatsarchiv (Veröffentlichungen aus dem Staatsarchiv der Freien und Hansestadt Hamburg, 2013)
In 2010, the Hamburg State Archives celebrated its 300th anniversary. The Archives' forerunner was first mentioned in 1293 and thus testified to the preservation of important documents of the city in a central place. But it was not until September 11th, 1710, when Nicolaus Stampeel took office as a scientific archivist at the City of Hamburg. From then on, documents were systematically selected, preserved and indexed.This anniversary was celebrated by the State Archives with a broad programme of events, which included lectures and readings printed in the commemorative volume available here.